Riesgos ambientales sobre agua y suelo por disposición de cortes de perforación en el Campo Castilla (2018)
The purpose of this monograph is to perform an analysis of the environmental risks caused by the provision of drilling cuts in the Campo Castilla de Ecopetrol. In order to obtain this objective, an investigation was made of the review of information in secondary sources and a descriptive analysis that allowed the identification of the environmental risks associated with this process, taking into account the geographic location and environmental conditions of Campo Castilla in the Meta and thus propose possible treatments for the risks identified there.